2007
DOI: 10.3168/jds.s0022-0302(07)71545-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somatic Cell Count on Prato Cheese Composition

Abstract: The objective of this research was to evaluate the effect of 2 levels of somatic cell counts (SCC) in raw milk on Prato cheese composition, protein and fat recovery, cheese yield, and ripening. A 2 x 6 factorial design with 3 replications was performed in this study: 2 levels of SCC and 6 levels of storage time. Initially, 2 groups of dairy cows were selected to obtain low (<200,000 cells/ mL) and high (>600,000 cells/mL) SCC in milks that were used to manufacture 2 vats of cheese: 1) low SCC and 2) high SCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
3
31

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 15 publications
8
45
3
31
Order By: Relevance
“…Thus, a higher loss of solids is expected to occur in whey from the pressed curd, used in cheddar cheese manufacturing, when compared with the nonpressed, high moisture minas frescal cheese. The results of the present study are consistent with those reported by Mazal et al (2007), who did not observe any significant difference in the yield of the semi-hard prato cheese manufactured from milk containing SCC at levels from 200,000 to 600,000 cells mL -1 .…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, a higher loss of solids is expected to occur in whey from the pressed curd, used in cheddar cheese manufacturing, when compared with the nonpressed, high moisture minas frescal cheese. The results of the present study are consistent with those reported by Mazal et al (2007), who did not observe any significant difference in the yield of the semi-hard prato cheese manufactured from milk containing SCC at levels from 200,000 to 600,000 cells mL -1 .…”
Section: Resultssupporting
confidence: 83%
“…In the present study, the failure of SCC in milk to affect the proteolysis of minas frescal cheese is in disagreement with previous reports that indicated that proteolysis was increased in cheddar cheese manufactured from milk with 500,000 cells mL -1 (Rogers & Mitchell, 1994), and in prato cheese made from milk with more than 600,000 cells mL -1 (Mazal et al, 2007). In fact, minas frescal is a nonripened cheese that is marketed for consumption immediately after manufacture.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…and the final quality of the product (taste, softness, melting, shelf life, etc.). Furthermore, the increase in processing time results in higher production costs for the industry and reduced profits (Mazal et al, 2007).…”
Section: Factors Regarding the Mozzarella Manufacturing Processmentioning
confidence: 99%